Los determinantes sociales del clima organizacional en la calidad del servicio administrativo de la red de salud trujillo - utes n° 6 trujillo este - año 2014 - Medina Vasquez, Malena Becky (2014)
In the present research is explained Influence of the Social Determinants of Organizational Climate in the Administrative Service Quality Health Network Trujillo UTES No.6, developed in 2013 The study was conducted through a sample of the staff working in the administrative headquarters of the Health Network Trujillo, using the deductive method - Inductive, Statistical and Analytical - Synthetic and techniques observation, informal interview and surveys. It was found that the social determinants of organizational climate as: interpersonal relationships and motivation in greater proportionality affect the dimensions of the quality of administrative service such as reliability and empathy. The results show that the fragility of the channels of communication between managers and employees, limits the right relationships, environments creates tension and does not allow employees to express their views or concerns freely and in turn limited staff morale administrative creates uncertainty in job stability. Quality runs showed that the dimensions of reliability and empathy, which are mostly limited quality service at the institution, because they don´t provide confidence to the user to wait for the requested service and offers the feel of individual treatment.